ANALISIS IMPLEMENTASI KEBIJAKAN PENGADAAN BARANG DAN JASA PEMERINTAH SECARA ELEKTRONIK (E-PROCUREMENT GOVERNMENT) DI PROVINSI JAWA BARAT - Yuli Hapiah (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
One of the current important topic to be dissect in the regional governing is the management of government's goods and services. This topic considered to be strategic and important in the effort of creating a good governance in the regionalgovernment. The strategic value lie in the creation of an efficient and effective goods and services, while the importance related to the effort on reducing corruption, collusion and nepotism and the creation of a good public accountability. Considering the importance of this topic for the regional government, the author compelled to analyse this subject, especially the ones related to the implementation of e-procurement policy by West Java Province's Communication and Informatics Agency